Nur mobile lab: a portable teaching aid - Jamaluddin, Nazhatulzalkis; Mizal Azzmi, Norazura; Ahzahar, Nadira; Hashim, Siti Zubaidah; Mohd Noor, Norehan@Norlida; Zakaria, ntan Bayani (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
The primary approach of comprehending lighting principles in the classroom is through verbal explanation. Thus, students encounter difficulties in visualizing the concepts and often experience confusion while acquiring knowledge of the fundamental principles of lighting. The Nur Mobile Lab aims to provide a visual demonstration of students' understanding in the fundamental principles of lighting within the classroom setting. The Nur Mobile Lab is a teaching aid constructed from plywood and acrylic Perspex materials. This innovative tool shows the principles of light. The innovation for a lighting box is a light, portable structure that is easy to carry to class to teach about artificial lighting as part of the Environmental Science subject. The objective of this subject is to provide the students with a fundamental knowledge of the methods employed by lighting practitioners for measurement purposes as well as the terminology commonly used in this field. Therefore, students can show their understanding of the subject by designing and calculating sufficient lighting in a space as required by the standards and regulations. The result of the final test also shows an increment in students’ grades, and the survey distributed reflects a positive outcome from the use of the tools. The Nur Mobile Lab assists students creative performance in learning through activities in the class.